Pengaruh Inovasi Produk dan Orientasi Pasar terhadap Kinerja Penjualan: (Studi Kasus pada Sentra Keripik Pisang di Jl. ZA. Pagar Alam Gang PU Bandar Lampung) - Andriyanto, Agung; Rinova, Dora; Oktavannur, M. (Business Perspective Journal, 2024)
This research aims to investigate the influence of product innovation and market orientation on sales performance, by taking a case study of the Banana Chips Center on Jalan Za. Pagar Alam Gang Pu, Bandar Lampung. Product innovation is identified as a key factor that is able to provide a company with a competitive advantage, while market orientation reflects the company's suitability in understanding and meeting market needs. In the context of the typical banana chips industry in Bandar Lampung, this study is relevant to explore the extent of the role of product innovation and market orientation in developing sales performance. This research uses a quantitative approach involving owners and managers of banana chip businesses and consumers as respondents. Data was collected through in-depth interviews, observations and questionnaires. Regression analysis is used to test hypotheses and analyze the extent of the influence of product innovation and market orientation on sales performance. The results of this research are that product innovation and market orientation have a significant effect on sales performance Keywords: product innovation; market orientation; sales performance